LANGFORD, Rosemary Teele. Company Directors’ Duties and Conflicts of Interest. - Martin Floreš (Časopis pro Právní Vědu a Praxi, 2021)
Recenze - LANGFORD, Rosemary Teele. Company Directors’ Duties and Conflicts of Interest Oxford: Oxford University Press, 2019, 465 s. ISBN 978-0-19-881366-8.